High-Performance Extremely Low-k Film Integration Technology with Metal Hard Mask Process for Cu Interconnects. (1st January 2016) - Torazawa, Naoki; Matsumoto, Susumu; Harada, Takeshi; Morinaga, Yasunori; Inagaki, Daisuke; Kabe, Tatsuya; Hirao, Shuji; Seo, Kohei; Suzuki, Shigeru; Korogi, Hayato; Okamura, Hideaki; Kanda, Yusuke; et al.
Abstract : High performance copper interconnects using extremely low-k film for the interlayer dielectric with the metal hard mask process and the interfacial surface oxygen treatment between extremely low-k film and liner layer was demonstrated. To suppress the process damage of interlayer dielectric and enlarge the space between vias and lines with a wide margin of lithography process, the robust extremely low-k film with the metal hard mask self-aligned via process was developed. The ultimate low capacitance wiring was achieved with the metal hard mask process, and the high reliability performance of time dependent dielectric breakdown between Cu lines with vias was accomplished by controlling the etching selectivity of the metal hard mask and the interlayer dielectrics. The adhesion strength between extremely low-k film and silicon carbide based liner layer was enhanced by controlling the composition of oxygen and carbon at the interface, resulting in the strengthening of the tolerance against chip packaging and thus the highly reliable chip packaging. This metal hard mask self-aligned via process with extremely low-k film and the interfacial surface oxygen treatment was demonstrated to be high performance, and therefore it offers a promising technology for Cu interconnects.